Implementasi Akad Percampuran dalam Hukum Ekonomi Syariah - Muhammad Turmudi (Al-'Adl, 2017)
Syirkah in Islamic economic law means the mixing of someone's property with others that begins with a contract / transaction so that between one part with another is difficult to distinguish. The mixing object consists of ay'n (real assets) in the form of goods and services and dayn (finan-cial assets) in the form of money and securities. Mixing Time consists of naqdan ie delivery at that time and ghairu naqdan surrender then or tough. In practice, Syirkah can be a mixing of 'ayn with' ayn, 'ayn with dayn and dayn with dayn. Shirkah has two main programs namely al-musharaka and al-mudaraba. Al-Musharaka is divided into shirkah amlak and syirkah 'uqud. musyarokah can be implemented in syariah banking through project financing and venture capital financing. Musyarokah is also implemented on Islamic insurance products, capital markets and SBSN / Sukuk. Al-Mudharabah differentiated into mudharabah muthlaqah, mudharabah muqayyadah and mudharabah musytarakah. Mudharabah in sharia banking and BMT is implementedin the form of saving futures, regular deposits and special deposits, working capital financing, special investments. Implementation of mudaraba in sharia insurance through premium from participant to insurance company and fund investment by insurance company to entrepreneur. Mudaraba also implemented in SBSN / Sukuk